Consensus Bundle on Severe Hypertension During Pregnancy and the Postpartum Period. (11th July 2017) - Bernstein, Peter S.; Martin, James N.; Barton, John R.; Shields, Laurence E.; Druzin, Maurice L.; Scavone, Barbara M.; Frost, Jennifer; Morton, Christine H.; Ruhl, Catherine; Slager, Joan; Tsigas, Eleni Z.; Jaffer, Sara; et al.
Abstract : Complications arising from hypertensive disorders of pregnancy are among the leading causes of preventable severe maternal morbidity and mortality. Timely and appropriate treatment has the potential to significantly reduce hypertension‐related complications. To assist health care providers in achieving this goal, this patient safety bundle provides guidance to coordinate and standardize the care provided to women with severe hypertension during pregnancy and the postpartum period. This is one of several patient safety bundles developed by multidisciplinary work groups of the National Partnership for Maternal Safety under the guidance of the Council on Patient Safety in Women's Health Care. These safety bundles outline critical clinical practices that should be implemented in every maternity care setting. Similar to other bundles that have been developed and promoted by the Partnership, the hypertension safety bundle is organized into four domains: Readiness, Recognition and Prevention, Response, and Reporting and Systems Learning . Although the bundle components may be adapted to meet the resources available in individual facilities, standardization within an institution is strongly encouraged. This commentary provides information to assist with bundle implementation.